2002
DOI: 10.1007/pl00007493
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of follicle number, serum estradiol level, and other factors to clinical pregnancy rate in gonadotropin-induced intrauterine insemination cycles

Abstract: The clinical pregnancy rate does not seem to be affected with the number of follicles present at the time of intrauterine insemination or the serum estradiol level at the day of hCG administration in a controlled ovarian hyperstimulation cycle in non-andrologic and non-peritubal factor infertility; however, there is a clear trend towards higher pregnancy rates with higher number of follicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
1
6
1
2
Order By: Relevance
“…Estrogen increases endometrial proliferation and uterine perfusion which improves the chance of pregnancy. E2 may disrupt the implantation process through endometrial damage which is responsible for the negative effect of E2 on IVF-ICSI outcome [9]. Despite the well-designed structure, the present study possesses some limitations, as follows (i) the number of included subjects was small (ii) no follow-up of patients for clinical pregnancy and live birth rate.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Estrogen increases endometrial proliferation and uterine perfusion which improves the chance of pregnancy. E2 may disrupt the implantation process through endometrial damage which is responsible for the negative effect of E2 on IVF-ICSI outcome [9]. Despite the well-designed structure, the present study possesses some limitations, as follows (i) the number of included subjects was small (ii) no follow-up of patients for clinical pregnancy and live birth rate.…”
Section: Discussionmentioning
confidence: 94%
“…Kyrou [7] have reported a lack of association in antagonist cycles and basal FSH [7]. Ozcakir et al [9] have evaluated this association after use of clomiphene citrate and HMG followed by intrauterine insemination of 180 patients and reported that there is no correlation between E2 level and clinical pregnancy [9]. Also, Mitwally et al [8] have investigated the association of E2 level during COH and peak E2 pregnancy outcome in 270 patients and reported the positive correlation between estradiol during COH and pregnancy outcome, but not between E2 on hCG administration day and pregnancy outcome.…”
Section: Discussionmentioning
confidence: 98%
“…Low total motile sperm count might not have been affected significantly in the second attempt. The outcome of COH-IUI cycles may be effected by many parameters such as, age, duration of infertility, dose of medication and the number of mature follicles 9,10 . In our study, there was no significant difference between the groups regarding these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled ovarian hyperstimulation (COH) combined with IUI may improve cycle fecundity rate compared with timed intercourse presumably due to increased number of oocytes available for fertilization 7,8 . Some factors such as sperm I count 9 and number of follicles developed have been positively related to pregnancy rate, whereas advanced female age and high cycle number have been negatively associated 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Peak estradiol should be a true reflection of the entire developing follicular cohort, both large- and intermediate-sized follicles. Some authors [8, 9] have found a correlation between peak estradiol and the number of follicles while others have not [11]. Adding to the confusion are significant differences between studies in terms of which follicle sizes they have considered “large” and whether they have used mean or largest diameter.…”
Section: Introductionmentioning
confidence: 99%